Pedagogical challenges in rural ESL multigrade classrooms in Malaysia: teachers’ perspectives teaching across grades - Tahir, Nur Anisah; Saad, Mohammad Azannee; Raja Abdul Razak, Raja Nurul Nadia; Satimin, Onaliza (Quantum Academic Publisher Enterprise, 2025)
Multigrade classrooms, where a single teacher instructs students from multiple grade levels simultaneously, are typical in rural and low enrolment schools. This study explores ESL teachers' pedagogical challenges in rural multigrade classrooms in Malaysia, where one teacher delivers instruction across multiple grade levels. Drawing from a qualitative research design, data were collected through semi-structured interviews involving eight ESL teachers from low enrolment schools in Peninsular Malaysia. The findings reveal various challenges, including institutional and professional constraints, complexities in managing diverse grade-level expectations, time limitations, student motivation and proficiency gaps, low parental engagement, and emotional and practical struggles in lesson delivery. These challenges significantly hinder teachers' ability to maintain consistent instructional quality and adapt materials effectively. The study highlights the pressing necessity for targeted professional development, contextualized teaching support, and policies tailored to the unique demands of multigrade ESL instruction in rural settings. By foregrounding the voices of teachers, this research provides insights into the lived realities of rural multigrade educators and calls for systemic reforms to support pedagogical sustainability.